Effect of different processing methods on physicochemical properties, chemical compositions and in vitro antioxidant activities of Paeonia lactiflora Pall seed oils. (1st December 2020) - Nie, Rong; Zhang, Yiren; Zhang, Hui; Jin, Qingzhe; Wu, Gangcheng; Wang, Xingguo
Highlights: SFE, ultrasonic-assisted solvent and pressing extraction methods were used. Characteristics of P. lactiflora oil were affected by extraction method and variety. SFE oil with higher percentage of tocopherol and phytosterols were determined. Pressed oil had the higher individual polyphenol content and antioxidant activity. Abstract: A research was performed to determine and compare the physicochemical properties, chemical compositions and in vitro antioxidant activities of Paeonia lactiflora Pall seed oils with ultrasonic-assisted solvent extraction, pressing and supercritical fluid extraction. Paeonia lactiflora Pall seed oil contained a high percentage of polyunsaturated fatty acids and monounsaturated fatty acids, especially oleic (31.62–32.88%) and α-linolenic acids (37.55–39.95%). The beneficial multiple dietary phytochemicals (tocopherol, phytosterols and squalene) and in vitro antioxidant activity were significantly influenced by the hull and processing method (P＜0.05). However, higher tocopherol (596.67–738.76 mg/kg) and phytosterols (5775.01–6055.62 mg/kg) contents were found in supercritical fluid extraction oils. Additionally, ten individual polyphenols were quantified, and significantly influenced by the hull and processing method (P＜0.05), with the content of benzoic acid and several individual flavonoids being the higher. According to the results, pressing might be the best process for extracting oil with a high number of polyphenols.